The Effect of Motivation and Work Discipline on Medical Staff Performance - Fachri, Muhammad (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
The purpose of this study departs from the problems that occur in Medical Personnel at the Budi Kasih Special Surgical Hospital in Majalengka Regency, related to Work Motivation, Work Discipline and Employee Performance, because there are still employees who do not understand a job, personality, professional and social and have not been able to use technology proficiently in the work process. The variables to be measured in this study are Work Motivation According to Maslow's Theory as quoted by Sondang P. Siagian (2013: 103) including Fulfillment of physical needs, Security needs, Social needs, Needs that reflect self-esteem, Actualization needs. Work Discipline According to Syarkani's Theory (2017: 368) including Punctuality, Using office equipment properly, High responsibility, Obedience to office rules. Employee Performance According to Robbins Theory (2016: 260) including Quality, Quantity, Accuracy, Effectiveness, Independence. The research method used is descriptive analytical research method through a quantitative approach. analysis that uses quantitative analysis tools, namely analysis tools that use models such as mathematical models, statistical and econometric models, how to collect data by using saturated sampling techniques on 35 respondents. The research instrument is in the form of a questionnaire containing statements to respondents using the Likert scale method using the theory from Sugiono (2013). The results of the correlation analysis calculation, there is a large influence with a value of 0.5 between variable X and variable Y. Determination analysis shows that it is known that the coefficient of determination is found in the Adjusted R Square value of 0.943, this means that the ability of the independent variable to explain the dependent variable is 94.3%, the remaining 5.7% of the explanation is the variable that affects but is not tested, the results of the clasi coefficient test state that H0 is rejected and H1 is accepted. Based on the results of the analysis of the discussion in this thesis, it is necessary to seek various actions to further enhance the role of employee performance and to improve or improve Work Motivation and Work Discipline of Medical Personnel at the Budi Kasih Specialized Surgical Hospital in Majalengka Regency Thus it can be concluded that there is an influence of motivation and work discipline on the performance of medical personnel at the Budi Kasih Specialized Surgical Hospital in Majalengka Regency.